The political meme: An analysis from a technological and democratic perspective (Research, Society and Development, 2021)
The article aims to analyze the memetic language in virtual space, in a democratic context and representation of political culture. The research is defined as qualitative and exploratory, with a bibliographic data collection technique. The results point to the memes' ability to communicate and disseminate ideas and opinions, with the potential to bring about changes in public opinion and influence electoral disputes, strengthening their democratic representation and political culture; but they also indicate the need to assess their ability to interact and produce meaning in the political scenario, so that the citizen is allowed greater political-democratic engagement.